Shocked titanite records Chicxulub hydrothermal alteration and impact age. (15th July 2020) - Timms, Nicholas E.; Kirkland, Christopher L.; Cavosie, Aaron J.; Rae, Auriol S.P.; Rickard, William D.A.; Evans, Noreen J.; Erickson, Timmons M.; Wittmann, Axel; Ferrière, Ludovic; Collins, Gareth S.; Gulick, Sean P.S.
Highlights: We present a new approach to dating hydrothermal activity in impact structures. A single, shocked, altered titanite grain from Chicxulub analysed by LA-ICPMS (n = 167). Alteration stripped trace elements along microcracks in titanite, resetting U-Pb age. Age of 67 ± 4 Ma in most altered zones dates the peak ring hydrothermal alteration. Depletion of REE-Y-Zr-Nb-Mo-Sn-Th-Pb has implications for titanite petrochronology. Abstract: Hydrothermal activity is a common phenomenon in the wake of impact events, yet identifying and dating impact hydrothermal systems can be challenging. This study provides the first detailed assessment of the effects of shock microstructures and impact-related alteration on the U-Pb systematics and trace elements of titanite (CaTiSiO5 ), focusing on shocked granite target rocks from the peak ring of the Chicxulub impact structure, Mexico. A > 1 mm long, shock-twinned titanite grain preserves a dense network of irregular microcracks, some of which exploit shock twin interfaces. Secondary microcrystalline anatase and pyrite are heterogeneously distributed along some microcracks. In situ laser ablation multi-collector inductively-coupled plasma mass spectrometry (LA-MC-ICPMS) analysis reveals a mixture of three end-member Pb components. The Pb components are: 1) common Pb, consistent with the Pb isotopic signature of adjacent alkali feldspar; 2) radiogenic Pb accumulated since magmatic crystallization; and 3) a secondary, younger Pb signature due to impact-related complete radiogenic Pb loss. The youngest derived ages define a regression from common Pb that intersects Concordia at 67 ± 4 Ma, in agreement with the established age of 66.04 ± 0.05 Ma for the Chicxulub impact event. Contour maps of LA-MC-ICPMS data reveal that the young ages are spatially restricted to microstructurally-complex domains that correlate with significant depletion in trace elements (REE-Y-Zr-Nb-Mo-Sn-Th) and reduction in magnitude of the Eu/Eu* anomaly. Mapping by time-of-flight secondary ion mass spectrometry (ToF-SIMS) show that patterns of localised element depletion in titanite are spatially related to microcracks, which are enriched in Al. The spatial correlation of ages and trace element abundance is consistent with localised removal of Pb and other trace elements from a pervasive network of fast fluid pathways in fractured domains via a fluid-mediated element transport process associated with the impact event. Here we interpret the 67 ± 4 Ma U-Pb age to represent hydrothermal Pb-loss in the Chicxulub peak ring in the wake of the impact event. These results highlight the potential of our analytical approach using titanite geochronology and geochemistry for dating post-impact hydrothermal activity in impact structures elsewhere.